Intra-gender violence in homosexual university students from Bucaramanga, Colombia - Redondo-Pacheco, Jesús; Rey-García, Pilar Alejandra; Ibarra-Mojica, Angela Nathalia; Luzardo-Briceño, Marianela (Universidad y Salud, 2021)
Introduction: Research on partner violence has mainly focused on studies of heterosexual couples, while data on same-sex dating violence are scarce. Objective: To analyze intra-gender violence in homosexual university couples in Bucaramanga. Materials and methods: A quantitative research with a snowball sampling approach was applied to obtain a population of 132 participants who were older than 18 years of age. The pre-validated instrument Check List for Partner Abuse Experience was used. Data were analyzed with SPSS software (version 23), using the X2 test and one-way ANOVA, considering an α=0.05. Results: 91.7% of participants experience violence with at least one of the studied behaviors. Psychological violence was the most predominant form in the studied couples, followed by emotional, physical, sexual, and economic violence. Significant differences between males and females were found for some items of the instrument. Conclusions: Psychological violence was the most frequent in the study’s participants.